Revolutionizing gifted education: enhancing teachers’ digital competence through fourth industrial revolution training - Abdulhamid Alarfaj; Mesfer Alrashidi (Discover Sustainability)
Abstract This study investigates the effectiveness of a specialized training program designed to enhance the Digital Competence (DC) of teachers of gifted students in Saudi Arabia within the context of Fourth Industrial Revolution (4IR) applications. Using a quasi-experimental design, 48 participants from Jubail were evaluated across pre-test, post-test, and follow-up stages utilizing a comprehensive digital competence questionnaire. Results indicate significant improvements in digital competence following the training, with sustained effectiveness evident in follow-up assessments. The program demonstrated value in equipping teachers with critical skills in areas such as Artificial Intelligence (AI), cybersecurity, big data, virtual reality, and digital content creation. These findings underscore the need to integrate advanced digital training into teacher education frameworks to address the evolving demands of contemporary education.